KAJIAN SEMANTIK PADA SAJAK SIA-SIA KARYA CHAIRIL ANWAR - Habibie, M. Baharuddin Yusuf; Setiawan, Hendra; Muhtarom, Imam (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This research discusses a semantic study of the poem